Inhibition of galectin‐3 augments the antitumor efficacy of PD‐L1 blockade in non‐small‐cell lung cancer. Issue 3 (31st January 2021) - Zhang, Hongxin; Liu, Pengfei; Zhang, Yan; Han, Lujun; Hu, Zhihui; Cai, Ziqi; Cai, Jianhui
Abstract : Multiple clinical trials have shown that monoclonal antibodies (mAbs) against programmed death‐ligand 1 (PD‐1/PD‐L1) can benefit patients with lung cancer by increasing their progression‐free survival and overall survival. However, a significant proportion of patients do not respond to anti‐PD‐1/PD‐L1 mAbs. In the present study, we investigated whether galectin (Gal)‐3 inhibitors can enhance the antitumor effect of PD‐L1 blockade. Using the NSCLC‐derived cell line A549, we examined the expression of Gal‐3 in lung cancer cells under hypoxic conditions and investigated the regulatory effect of Gal‐3 on PD‐L1 expression, which is mediated by the STAT3 pathway. We also explored whether Gal‐3 inhibition can facilitate the cytotoxic effect of T cells induced by PD‐L1 blockade. The effects of combined use of a Gal‐3 inhibitor and PD‐L1 blockade on tumor growth and T‐cell function were also investigated, and we found that hypoxia increased the expression and secretion of Gal‐3 by lung cancer cells. Gal‐3 increased PD‐L1 expression via the upregulation of STAT3 phosphorylation, and administration of a Gal‐3 inhibitor enhanced the effect of PD‐L1 blockade on the cytotoxic activity of T cells against cancer cells in vitro . In a mouse xenograft model, the combination of a Gal‐3 inhibitor and PD‐L1 blockade synergistically suppressed tumor growth. Furthermore, the administration of a Gal‐3 inhibitor enhanced T‐cell infiltration and granzyme B release in tumors. Collectively, our results show that Gal‐3 increases PD‐L1 expression in lung cancer cells and that the administration of a Gal‐3 inhibitor as an adjuvant enhanced the antitumor activity of PD‐L1 blockade. Abstract : Galectin (Gal)‐3 is involved in the immune response, and highly overexpressed and secreted by lung cancer cells. This study showed that the increased expression of Gal‐3 was induced by hypoxia, which then contributed to immune suppression through the STAT3 pathway in lung cancer. Furthermore, a Gal‐3 inhibitor enhanced the antitumor effect by PD‐L1 blockade through promoting T‐cell infiltration in lung cancer.